The effects of timing on the cost-effectiveness of interventions for workers on sick leave due to low back pain. Issue 11 (10th September 2010) - van Duijn, Miranda; Eijkemans, Marinus J; Koes, Bart W; Koopmanschap, Marc A; Burton, Kim A; Burdorf, Alex
Abstract : Objective: To examine the effects of different timing of structured interventions for workers on sick leave due to low back pain on return to work (RTW), and the consequences for costs and benefits. Methods: Literature reviews were conducted to identify RTW curves and to estimate treatment effects, costs and benefits of structured interventions among workers on sick leave due to low back pain. RTW curves were mathematically described by Weibull functions and intervention effects, expressed by hazard ratios, were used to adjust these Weibull functions. Subsequently, these functions were used to evaluate the theoretical effects of interventions on reduction in number of days on sick leave and on the benefit–cost ratio. Results: The cost-benefits of a RTW intervention among workers on sick leave due to low back pain were determined by the estimated effectiveness of the intervention, the costs of the intervention, the natural course of RTW in the target population, the timing of the enrolment of subjects into the intervention, and the duration of the intervention. Conclusion: With a good RTW in the first weeks, the only early interventions likely to be cost-beneficial are inexpensive work-focused enhancements to early routine care, such as accommodating workplaces. Structured interventions are unlikely to have an additional impact on the already good prognosis when offered before the optimal time window at approximately 8 to 12 weeks. The generalisibility of the effectiveness of a RTW intervention depends on the comparability of baseline characteristics and RTW curves in target and source populations.